2017
DOI: 10.18632/oncotarget.19359
|View full text |Cite
|
Sign up to set email alerts
|

Association of myelinated primary afferents impairment with mechanical allodynia in diabetic peripheral neuropathy: an experimental study in rats

Abstract: To investigate the mechanisms underlying the efficacy of surgical treatment for painful diabetic peripheral neuropathy. Rats were initially divided into 3 groups (I, control rats, II, streptozotocin-induced diabetic rats, III, streptozotocin-induced diabetic rats with latex tube encircling the sciatic nerve without compression). When mechanical allodynia (MA) became stable in the third week, one third of group III rats were sacrificed and the remainder were further divided into subgroups depending on whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…21 However, hyperglycemia and DPN was induced well, with the rats remaining otherwise relatively healthy according to our experience. 22 In the present study, both mechanical allodynia and thermal hyperalgesia were observed to manifest in both STZ-induced diabetic groups. In accordance with previous literature, a high incidence of thermal hyperalgesia (90.0%) and a moderate incidence (57.1%) of mechanical allodynia by STZ-injection were observed.…”
Section: Discussionsupporting
confidence: 55%
“…21 However, hyperglycemia and DPN was induced well, with the rats remaining otherwise relatively healthy according to our experience. 22 In the present study, both mechanical allodynia and thermal hyperalgesia were observed to manifest in both STZ-induced diabetic groups. In accordance with previous literature, a high incidence of thermal hyperalgesia (90.0%) and a moderate incidence (57.1%) of mechanical allodynia by STZ-injection were observed.…”
Section: Discussionsupporting
confidence: 55%
“…Numerous mainstream academic groups, including American Diabetes Association, are strongly advocating for clinical trials with high-level evidence to determine whether surgical decompression is beneficial ( 25 , 26 , 46 ). The present trial is conducted based on our previous clinical and translational studies, in which we investigated the factors associated with a favorable surgical outcome and explored the pathological mechanisms underlying painful DPN ( 17 , 35 , 47 , 48 ). According to our previous clinical practice, diabetic patients with higher VAS are more likely to seek surgical consultants than those with lower VAS.…”
Section: Discussionmentioning
confidence: 99%